Heart failure with normal LVEF in BIOSTAT-CHF. (1st October 2022) - Baumhove, Lukas; Tromp, Jasper; Figarska, Sylwia; van Essen, Bart J.; Anker, Stefan D.; Dickstein, Kenneth; Cleland, John G.; Lang, Chim C.; Filippatos, Gerasimos; Ng, Leong L.; Samani, Nilesh J.; Metra, Marco; et al.
Abstract: Aims: Several studies have shown that heart failure (HF) drug treatment seems to benefit patients with preserved ejection fraction (HFpEF) and a left ventricular ejection fraction (LVEF) up to 55–60% but not with higher LVEF. Certain HF drugs are now indicated in patients with HFpEF and a LVEF below normal. However, not much is known about patients with a normal LVEF. Therefore, we investigated the prevalence, clinical characteristics and outcome of patients with HF and a normal LVEF. Methods and results: Normal LVEF was defined according to the Recommendations for Cardiac Chamber Quantification from the American Society of Echocardiography as a LVEF ≥62% for men and ≥ 64% for women. Preserved ejection fraction was defined as a LVEF ≥50% and reduced ejection fraction as a LVEF <50%. In the total cohort of 1568 studied patients with heart failure (mean age 73 years; 33.6% female) 57 patients (3.6%) had a normal LVEF. These patients least likely had a previous myocardial infarction ( p < 0.001) or diabetes ( p = 0.045), had the lowest Left Ventricular End Diastolic Diameter ( p < 0.001), the highest rate of previous HF hospitalization in the last year ( p = 0.015), the highest cardiac output ( p < 0.001) and were most frequently women ( p < 0.001). Patients with a normal LVEF had the lowest risk for the primary combined outcome of all-cause mortality and HF hospitalization. Conclusion: Only 3.6% of patients with HF had a sex-adjusted normal LVEF. Despite the sex-adjusted cut-offs they were more frequently female with less ischemic heart disease, higher cardiac output and better clinical outcomes. Highlights: Only 3.6% of patients with HF had a sex-adjusted normal LVEF. Patients with a normal LVEF were most commonly women with less ischemic heart disease and diabetes. They had the lowest risk for the primary combined outcome of all-cause mortality and HF hospitalization.